Transcriptome Analysis Reveals Putative Target Genes of APETALA3-3 During Early Floral Development in Nigella damascena L. - Deveaux, Yves; Conde e Silva, Natalia; Manicacci, Domenica; Le Guilloux, Martine; Brunaud, Véronique; Belcram, Harry; Joets, Johann; Soubigou-Taconnat, Ludivine; Delannoy, Etienne; Corti, Hélène; Balzergue, Sandrine; Caius, Jose; et al. (Frontiers in Plant Science, 2021)
Even though petals are homoplastic structures, their identity consistently involves genes of the APETALA3 lineage. However, the extent to which the networks downstream of AP3 are conserved in species with petals of different evolutionary origin is unknown. In Ranunculaceae, the specificity of the AP3-III lineage offers a great opportunity to identify the petal gene regulatory network in a comparative framework. Using a transcriptomic approach, we investigated putative target genes of the AP3-III ortholog NdAP3-3 in Nigella damascena at early developmental stages when petal identity is determined, and we compared our data with that from selected eudicot species. We generated a de novo reference transcriptome to carry out a differential gene expression analysis between the wild-type and mutant NdAP3-3 genotypes differing by the presence vs absence of petals at early stages of floral development. Among the 1,620 genes that were significantly differentially expressed between the two genotypes, functional annotation suggested a large involvement of nuclear activities, including regulation of transcription, and an enrichment in processes linked to cell proliferation. Comparing with Arabidopsis data, we found that highly conserved genes between the two species are enriched in homologs of direct targets of the AtAP3 protein. Integrating AP3-3 binding site data from another Ranunculaceae species, Aquilegia coerulea, allowed us to identify a set of 18 putative target genes that were conserved between the three species. Our results suggest that, despite the independent evolutionary origin of petals in core eudicots and Ranunculaceae, a small conserved set of genes determines petal identity and early development in these taxa.